How Do Chinese Firms Deal with Inter-Organizational Conflict? - Mo, Shenjiang; Booth, Simon A.; Wang, Zhongming (2012)
Based on social exchange and customer relationship marketing theory, this study examines how ethical leadership contributes to inter-organizational conflict management (task conflict (TC) and relationship conflict), and the moderating role of task interdependence in these relationships. Data was collected from 81 suppliers and 45 corresponding managers of a large group company in China. Results show that ethical leadership is negatively associated with the levels of inter-organizational conflict, whether task or relationship. Task interdependence significantly moderates the relationship between ethical leadership and TC. Managerial implication in terms of creating sound buyer–supplier relationship through an ethical perspective is discussed.
Keywords: Inter-organizational relationship; Task interdependence; Relationship conflict; Task conflict; Ethical Leadership